2018
DOI: 10.5688/ajpe6220
|View full text |Cite
|
Sign up to set email alerts
|

Student and School-level Predictors of Pharmacy Residency Attainment

Abstract: Objective. To identify student and school level predictors of pharmacy residency attainment. Methods. Data were collected from the American Association of Colleges of Pharmacy (AACP) and the Carnegie Classification of Institutions of Higher Education. Logistic multilevel modeling was used to examine the effects of select student and school level characteristics on pharmacy residency attainment, as indicated by students on the AACP Graduating Student Survey (GSS) from 2013 to 2015.Results. The dataset included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Two articles were found that described the use of data from the CQS surveys to evaluate and improve programs. 3,4 Haines and colleagues developed a mentoring program in response to low scores on the faculty survey. 3 Graduating student survey responses were utilized by Lyons and Colleges to assess student and school-level predictors of pharmacy residency attainment.…”
Section: A J P Ementioning
confidence: 99%
See 1 more Smart Citation
“…Two articles were found that described the use of data from the CQS surveys to evaluate and improve programs. 3,4 Haines and colleagues developed a mentoring program in response to low scores on the faculty survey. 3 Graduating student survey responses were utilized by Lyons and Colleges to assess student and school-level predictors of pharmacy residency attainment.…”
Section: A J P Ementioning
confidence: 99%
“…3 Graduating student survey responses were utilized by Lyons and Colleges to assess student and school-level predictors of pharmacy residency attainment. 4 However, there is a lack of literature to drive best practices as to how S/COP should use this data to make improvements to their program. Instead, most information available to S/COP resides in the "good use" document, but it is unknown the level to which S/COP utilize this tool.…”
Section: A J P Ementioning
confidence: 99%
“…1 In some cases, data collected for operational purposes might also be used for research, such as examining residency attainment across pharmacy schools. 2 Pharmacy educators and educational researchers increasingly rely on computational tools to act on a wide range of data types, formats, and protocols that support empirical research and decision-making. If you consider a student's entire educational record, for example, there might be numeric data related to admissions, course grades, class attendance, objective structured clinical examination (OSCE) ratings, experiential grades, Pharmacy Curriculum Outcomes Assessment (PCOA) scores, a North American Pharmacy Licensing Examination (NAPLEX) score, and demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…6 The qualities desired in an ideal residency candidate, however, extend beyond clinical experience alone and include knowledge of and experience in scholarship, teaching, and leadership. [9][10][11][12] To date, there have been no published reports describing a formalized program that provides students with mentorship and advanced training in the area most valued by residency programs (ie, clinical practice, teaching, research/ scholarship, and leadership).…”
Section: Introductionmentioning
confidence: 99%